Physical and Sensory Characteristics of Gluten Free Cookies Prepared from Black Glutinous Rice and MOCAF Flour Combination - Destiana Adinda Putri; Husnita Komalasari; Devy Ulandari; Fuad Sauqi Isnain (Universitas Slamet Riyadi Surakarta, 2023)
Extensive research has been conducted to investigate the formulation of a new generation of cereal-based Gluten Free (GF) foods formulated with High-Resistant Starch (RS) sources and high in nutritional value. Black glutinous rice flour is a rich in bioactive compound and MOCAF is known for its high RS content often used as an alternative to wheat flour in the production of gluten-free cookies. The formulation of the combination of these two ingredients needs to be investigated to produce gluten free cookies that have good physical and sensory characteristics. The aims of these research was to investigate the effect of different ratio of Black Glutinous Rice Flour (BGRF) and MOCAF (MF) formulation (F1 = 100:0, F2= 75:25, F3=50:50, F4= 25:75, F5= 0:100) on physical and sensory parameter of resultant GF cookies. The results shows that, cookies with high amount of BGRF showed interesting physical properties with higher diameter, spread ratio, and ∆E of the cookies, lower weight, thickness, baking loss, L*, a*, b*, C* value, and the hedonic score of color, aroma, taste, texture, overall compared to cookies with 100% MF. The best formula that produces gluten free cookies with the highest taste score score is F4 (BGRF 25%:MF 75%) with physical characteristics weight 10.70 g, diameter 48.40 mm, thickness 8.60 mm, spread ratio 5.63, baking loss 17.37 %, L* 53.96, a* 0.63, b* 17.65, C* 17.66, ∆E 48.78. With the combination of BGRF and MF on cookies dough, we manage to obtain cookies that has great potential to increase the nutritional quality of gluten-free food.